Photini Danou, Η Λερναία Ύδρα των Αχρείων: Τα πληβεία στρώματα στην αγγλική πολιτική σκέψη (1509-1625) [The hydra of the vile: plebeians in English political theory, 1509-1625] - Liapi, Lena (Historein, 2018)
Review of Photini Danou. Η Λερναία Ύδρα των Αχρείων: Τα πληβεία στρώματα στην αγγλική πολιτική σκέψη (1509-1625) [The hydra of the vile: plebeians in English political theory, 1509-1625]. Athens: Irodotos, 2017. 156 pp.